Effect of Phytase Supplementation on Nutrients Availability and Performance of Broiler Chicks - Rezaei, M.; Borbor, S.; Zaghari, M.; Teimouri, A. (International Journal of Poultry Science, 2006)
An experiment was conducted to determine the effect of phytase supplementation on broiler performance and evaluation of nutrients equivalency for Natuphos phytase, using 640 day-old commercial broiler chickens from 1 to 49 days of age. The experimental units were allocated randomly to 4 dietary treatments x two sexes with 4 replicates per treatment. The first dietary treatment formulated without phytase, the second one contained 500 FTU/kg phytase, and the third one contained 500 FTU/kg phytase which was calculated half of the nutrients equivalency values for phyatse. The fourth dietary treatment contained 500 FTU/kg phyatse which was calculated the total nutrients equivalency values for phytase. During the experiment feed intake, body weight gain, and feed conversion ratio (FCR) were measured in each phase of the rearing. Mortality was recorded throughout the experiment. No significant difference was observed among four dietary treatments for final body weight, feed conversion ratio and carcass characteristics (p>0.05). The results indicated that phytase increased the availability of nutrients in third and fourth treatments. Toe ash, and toe ash Ca and P percentage increased with the addition of phytase in both sexes (p< 0.05), but had no significant effect on blood phosphorus concentration.